The Mediating Role of Academic Resilience in the Relationship Between Positive Emotions and Test Anxiety Among Muslim Undergraduate Students - Ghareib, Hamed Samy; Al-Osail, Abdulaziz Faleh; Abdellatif, Mohamed Sayed; Ibrahim, Ashraf Ragab; Al-Dosari, Mashael Nasser; Nemt-allah, Mohamed Ali (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2026)
While positive emotions and test anxiety have been extensively studied in educational psychology, the mechanisms linking these constructs remain insufficiently understood, particularly within Islamic higher education. This study investigated whether academic resilience mediates the relationship between positive emotions and test anxiety among Muslim undergraduate students at Al-Azhar University. A cross-sectional design was employed with 300 students (144 males, 156 females; Mage = 20.20, SD = 0.94) from the Faculty of Education, Al-Azhar University, Egypt. Participants completed the Academic Resilience Scale-30, a newly developed 27-item Arabic Positive Emotion Scale, and the Multidimensional Test Anxiety Scale. Mediation analysis using Hayes' PROCESS macro with 5,000 bootstrap samples revealed significant correlations: positive emotions correlated positively with academic resilience (r =.489, p <.001) and negatively with test anxiety (r = -.322, p <.001), while academic resilience negatively correlated with test anxiety (r = -.290, p <.001). The analysis confirmed partial mediation, with positive emotions significantly predicting academic resilience (β =.489, p <.001), which in turn predicted reduced test anxiety (β = -.174, p =.005). The indirect effect was significant (β = -.085), accounting for 26.42% of the total effect, while the direct effect remained significant (β = -.237, p <.001), representing 73.58% of the relationship. Results demonstrate that academic resilience is a partial mediator, with positive emotions operating through direct and indirect pathways to reduce test anxiety. These findings reveal significant associations among positive emotions, academic resilience, and test anxiety, suggesting that these constructs may be potential targets for future anxiety interventions that could integrate immediate positive emotion strategies (e.g., gratitude practices, spiritual mindfulness) and longer-term resilience-building components (e.g., adaptive help-seeking, perseverance development) within Islamic educational frameworks, though longitudinal and intervention research is needed to establish causal relationships and intervention effectiveness.